(untitled) (Psychology Travelogs, 2023)
The article analyzes the views of ancient philosophers on the problem of the interaction of soul and body. It is proved that in antiquity there were two main approaches to understanding the mentioned problem: Plato’s approach (the soul was considered as the subject of activity in relation to the body) and Aristotle’s approach (he emphasized the mutual influences of body and soul). It is substantiated that these approaches do not contradict each other, but complement each other. Plato’s views were developed by Christian thinkers and theologians to emphasize the importance of the human mind and its ability to control bodily needs. It is substantiated that Aristotle’s views laid the philosophical foundation of psychosomatics. Platon initiates a metaphysical approach to the interaction of soul and body: the soul (mind) must control bodily needs. The philosopher described the relationship between soul and body (mind and body), which is inherent in individuals. He examines the problem of soul and body in the context of epistemological and ethical problems. This approach was significantly ahead of its time and remains relevant to this day. Plato laid the foundation for the Christian understanding of the interaction of soul and body and assigns responsibility for the development of the soul to man. Aristotle investigates the dialectic of the interaction between the soul and the body from the standpoint of ontology, he emphasized the dependence of mental states on the state of the body. This approach describes the interaction between the soul and body of the average person. Stagirite’s emphasis on the mutual influences of soul and body should be placed in the theoretical foundations of psychosomatics. It is not worth contrasting the views of Plato and Aristotle regarding the relationship between the soul and the body, because they complement each other.